Analysis of employee performance through productivity: The role of kaizen culture, motivation, and work discipline in the manufacturing industry - Ichdan, Dany Amrul (Goodwood Publishing, 2024)
Purpose: This study investigates the relationship between employee performance and productivity in the manufacturing industry, focusing on the impact of Kaizen culture, motivation, and work discipline on employee performance. Research Methodology: The study employed a quantitative method approach, which involved a survey of 105 respondents from the manufacturing Industry in West Java, and the analysis of key performance indicators from several pilot case companies in Bekasi that implemented Kaizen techniques. Data were analyzed using the SmartPLS test. Results: Kaizen culture, motivation, and work discipline are vital for improving employee performance and productivity. Employee motivation directly influences the implementation of the 5S system, and the company meets employees’ needs for career development and information. Employee performance is influenced by motivation, discipline, training, and culture, with productivity as the mediator. Limitations: The generalizability of this study is limited by its focus on a specific industry and geographic location. Future studies should replicate the study across different industries and regions to increase the scope of the findings. Contribution: This study contributes to the current literature by examining how Kaizen culture, motivation, and work discipline boost employee performance and productivity in manufacturing. The results underscore the significance of these elements in enhancing organizational performance and offer practical suggestions for companies that aim to enhance productivity and employee engagement. Originality: This study is unique in its thorough examination of how Kaizen culture, motivation, and work discipline affect employee performance and productivity in manufacturing. Using quantitative methods and diverse data sources enhances originality and offers a deeper understanding of these factors.